2011
DOI: 10.1083/jcb1942oia6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor restricts hematopoietic stem cell activity in mice: involvement of two distinct receptors

Abstract: Whereas maintenance of hematopoietic stem cells (HSCs) is a requisite for life, uncontrolled expansion of HSCs might enhance the propensity for leukemic transformation. Accordingly, HSC numbers are tightly regulated. The identification of physical cellular HSC niches has underscored the importance of extrinsic regulators of HSC homeostasis. However, whereas extrinsic positive regulators of HSCs have been identified, opposing extrinsic repressors of HSC expansion in vivo have yet to be described. Like many othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 24 publications
5
73
0
Order By: Relevance
“…on May 11, 2018. by guest www.bloodjournal.org From myelosuppression, we found (albeit not significant) increased levels of TNF␣, a suppressor of normal HSC activity, 38 in the BMEF of MM patients that has been shown to inhibit erythroid colony formation of HSPCs via activation of NFKB signaling. 39 It is therefore conceivable that activation of these pathways contributes to the observed deregulation of HSPC, although inhibition of p38 MAPK and NF-B signaling did not restore clonogenic capacities of the MM HSPCs examined.…”
Section: Discussionmentioning
confidence: 74%
“…on May 11, 2018. by guest www.bloodjournal.org From myelosuppression, we found (albeit not significant) increased levels of TNF␣, a suppressor of normal HSC activity, 38 in the BMEF of MM patients that has been shown to inhibit erythroid colony formation of HSPCs via activation of NFKB signaling. 39 It is therefore conceivable that activation of these pathways contributes to the observed deregulation of HSPC, although inhibition of p38 MAPK and NF-B signaling did not restore clonogenic capacities of the MM HSPCs examined.…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, in the hematopoietic system, TNF was shown to have a stimulatory growth effect on hematopoietic stem cells (HSCs) but to negatively regulate the growth of their more mature progenitors in vitro [71]. In contrast, recent findings revealed that TNF suppresses cycling HSCs and their longterm repopulating activity in vivo [72] and in vitro [73], indicating that although the TNF pathway is a critical regulator of HSC maintenance and function (reviewed in [47]), the stimulatory and/or repressive effect of TNF will depend on cell types, the responding compartment and the cell status within each compartment. Little is known concerning the effect of TNF on the melanoma SC compartment.…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of long-term hematopoietic stem cells (LT-HSC), shortterm HSC (ST-HSC), and multipotent progenitors (MPP) (27,28), splenocytes or bone marrow cells were incubated with biotinylated Lin markerspecific Abs (except anti-CD127), then with streptavidin-PerCP, and finally with fluorescently labeled Abs to CD117, Sca-1, CD150, and CD135.…”
Section: Flow Cytometry Analyses and Cell Sortingmentioning
confidence: 99%